Stabilitas Kimiawi Sirup Ekstrak Etanolik Bunga Kembang Sepatu (Hibiscus rosa-sinensis L.) - PRAISELA RIZDHANIA; MIMIEK MURRUKMIHADI; Iswandi - (Fakultas Farmasi Universitas Setia Budi, 2012)
The ethanolic extract of hibiscus flower (Hibiscus rosa-sinensis L.) on concentration 1,25% had mucolytic effect (Septyani 2009) with alkaloid as its marker substances. Syrup was suitable because its local effect so mucus will be able to go off easily. The aim of this research was to determined chemical stability of syrup based on optimum formulation by reduction value of alkaloid as its parameter. Hibiscus powder was extracted using maceration method with PE and its residue remacerated by ethanol 70%. Standard curve was made from isolate of alkaloid with various concentration on 5; 2,5; 1,25; 0,625; and 0,3125 μg/μl with regressional equation Y = -2,225 + 16,777 x. Syrup has been made in 3 formulation with various extract concentration on 1,00; 1,25; and 1,50%. Its physical stability including viscosity and decanted easily test has been checked then the chemical stability has been done by heated syrup on increasing term from 40º, 55ºC and 70ºC. The reduction of stability known by reduction of alkaloid value as AUC from densitometer. It was analyzed using Anova two ways followed by Dunnett T3 with significancy (p 0,05). The result showed that increasing term was influence to reduction of alkaloid value but various extract concentrations were not. So it was concluded that syrup with 1,25% extract concentration had the best stability.